A study on the perinatal outcome in cases of oligohydramnios - Kaur, Pawanpreet; Desai, Deepak A.; Taraiya, Aartee (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Amniotic fluid has an important role in the fetal growth and development. It provides the fetus, with a protective low resistance environment which is suitable for the growth and development. With normal amount of amniotic fluid index ranging from 5 to 24 cms, Amniotic fluid index of <5 cm defines oligohydramnios as, originally described by Phelan et al1. Many studies show that oligohydramnios is associated with variety of ominous pregnancy outcomes, such as fetal distress, low birth weight, increased incidence of caesarean section, higher perinatal morbidity, and perinatal mortality. Since, these disorders of liquor amnii has a significant impact on pregnancy and fetus, it prompted us to carry out this study with sincere efforts to find out its effect on pregnancy outcome. Methods: The study was done in Dhiraj Hospital in Obstetrics and Gynecology department. The study duration was period of 18 months from February 2014 to July 2015. It was a prospective study, comprising of patients, who had reported to hospital for regular antenatal visits. The study group was taken on sole criteria of AFI <5cms. It is considered as a contributing factor for intranatal and perinatal morbidity. To prove our point, in control group, patients with AFI >5 cms were taken. AFI >10 cms was considered to be normal. Various outcome measures recorded were, induced Vs spontaneous labor, gestational age at delivery, nature of amniotic fluid, FHR tracings, mode of delivery, indication for cesarean section or instrumental delivery Apgar score at one minute and five minutes, birth weight, admission to neonatal intensive care unit, perinatal morbidity and perinatal mortality. Results: Normal quantity of liquor amnii is essential for normal and successful outcome of pregnancy, as it provides a safe milieu interior for the foetus in utero. Deprivation of required quantity, will adversely affect the neonatal outcome. Oligohydramnios, in itself is enough to cause such damage, by creating chronic hypoxic situation. Conclusions: The fetal morbidity and mortality increases if additional antenatal complications of preeclampsia and post-term pregnancy are present along with oligohyrdramnios.